2021
DOI: 10.21873/invivo.12457
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin in the Surgical Treatment of Complex Abdominal Hernias: A Surgical Anatomy Approach, Current Evidence and Outcomes

Abstract: Background/Aim: Abdominal wall hernias represent a common problem in surgical practice. A significant proportion of them entails large defects, often difficult to primarily close without advanced techniques. Injection of botulinum toxin preoperatively at specific points targeting lateral abdominal wall musculature has been recently introduced as an adjunct in achieving primary fascia closure rates. Materials and Methods: A literature search was conducted investigating the role of botulinum toxin in abdominal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
2
2
0
6
Order By: Relevance
“…A statistically significant decrease in the size of the transverse hernia defect and loss of domain following the Botox injection supported the study's findings that Botox injection was beneficial in easing muscular tension and attaining primary fascial closure. The study's results are in line with other research that showed how well Botox injections could help patients with complicated abdominal wall hernias by easing muscular tension and promoting primary fascial closure [20,21]. Following the Botox injection, there was a statistically significant decrease in the size of the transverse hernia defect (p 0.001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A statistically significant decrease in the size of the transverse hernia defect and loss of domain following the Botox injection supported the study's findings that Botox injection was beneficial in easing muscular tension and attaining primary fascial closure. The study's results are in line with other research that showed how well Botox injections could help patients with complicated abdominal wall hernias by easing muscular tension and promoting primary fascial closure [20,21]. Following the Botox injection, there was a statistically significant decrease in the size of the transverse hernia defect (p 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Some individuals complained of minor discomfort and bruising near the injection sites, although these side effects quickly disappeared on their own. The lack of significant side effects is consistent with earlier research that found Botox injections were safe for people with complicated abdominal wall hernias [11,20]. Botox injection is a low-risk, minimally intrusive technique that can be carried out while receiving a local anesthetic [6].…”
Section: Discussionsupporting
confidence: 86%
“…Progressive preoperative pneumoperitoneum to augment hernia sac volume and native abdominal cavity volume can be added to chemical component separation, thus further enhancing the ability to tackle complex hernias [57]. Of notice, chemical component separation, which induces temporary paralysis of abdominal wall muscles only, can have a differential effect on hernia sac versus the native abdominal cavity, thus creating a selective effect of progressive preoperative pneumoperitoneum on abdominal wall prehabilitation, essentially, canceling its otherwise non-selective nature of action on both the hernia sac volume and native abdominal cavity volume, which theoretically leaves the aforementioned ratio of them unaltered [58].…”
Section: Preoperative Planning -Abdominal Wall Prehabilitationmentioning
confidence: 99%
“…4 Esta neurotoxina faz com que ocorra paralisia dos músculos da parede abdominal sem alterar sua constituição, aumentando a flexibilidade e reduzindo a força lateral em esforço para facilitar o fechamento da linha média, permitindo reconstrução cirúrgica. 4,7,12,[16][17][18][19][20][21] A injeção da TBA é mais comumente realizada guiada por ultrassom, geralmente nos músculos oblíquos externo e interno e também no músculo transverso do abdome bilateralmente. 19,21 O sistema do CPN abdominal gera pressão negativa centrípeta contínua, que promove a aproximação facial e a evacuação do exsudato inflamatório.…”
Section: Introductionunclassified
“…4,7,12,[16][17][18][19][20][21] A injeção da TBA é mais comumente realizada guiada por ultrassom, geralmente nos músculos oblíquos externo e interno e também no músculo transverso do abdome bilateralmente. 19,21 O sistema do CPN abdominal gera pressão negativa centrípeta contínua, que promove a aproximação facial e a evacuação do exsudato inflamatório. Também ajuda a proteger o conteúdo abdominal do ambiente externo, fornece separação entre a parede abdominal e as vísceras e protege o conteúdo abdominal, permitindo acesso rápido para revisão da cavidade 22 sendo mais um recurso na tentativa da reconstrução da parede abdominal.…”
Section: Introductionunclassified